The emotional intelligence of pediatric residents – a descriptive cross-sectional study - McLeod, Scott Alexander; Sonnenberg, Lyn K. (Canadian Medical Education Journal, 2017)
Background: Emotional Intelligence (EI) is a type of social intelligence. Excellent scores are achieved by displaying high levels of empathy in interpersonal relationships, strong skills in managing stressful situations as well as other personal competencies. Many of the social competencies that EI describes may have a direct impact on patient care. The objective of this study was to describe EI of pediatric residents and to identify if there are EI skills that should be selected for targeted intervention. Methods: This was a cross-sectional study administering the EQ-i 2.0© psychometric instrument to pediatric residents at the University of Alberta. Results: Thirty-five residents completed the EQ-i 2.0© (100% response rate). Their overall EI score was not significantly different than a normative group of college-educated professionals. Residents had relative strengths in the subcategories of Emotional expression, Interpersonal Relationships, Empathy, and Impulse Control (all p<0.05). Areas of relative weakness were in the subcategories of Stress Tolerance, Assertiveness, Independence, and Problem Solving (all p<0.05). Conclusion: The EI of pediatric residents is consistent with that of other professionals. Educational interventions may be useful in the areas of weakness to enhance the physician-patient relationship.